The Weather Underwater: Blackness, White Feminism, and the Breathless Sea. Issue 102 (2nd October 2019) - Neimanis, Astrida
ABSTRACT: This article offers a feminist environmental response to 'the breathless sea'. Through a close reading of [Christina Sharpe's. 2016. The Wake: On Blackness and Being . Durham: Duke University Press]; Adrienne Rich's. 1973. "Diving into the Wreck." In Diving into the Wreck: Poems 1971–1972 . New York: WW Norton; and Alexis Pauline Gumbs'. 2018. M Archive: After the End of the World . Durham: Duke University Press], it explores the increasingly vulnerable ocean both as a site of environmental damage, and as a speculative meeting place between black feminist poetics and white feminism. A series of interconnected arguments unfold: (1) learning from Sharpe, the weather is understood as not only climatological but also in terms of the 'total climate' that is antiblackness; (2) the ocean is not immune from weather; the weather underwater comprises anthropogenic harm to oceans (including increasing levels of oxygen depletion), but also the legacy of antiblackness; (3) from an environmental humanities perspective, the 'wreck' of Rich's poem is not only a 'wrecked' gender order, but also the ecological damage of the undersea; white feminism, however, struggles to notice that this 'wreck' is also antiblackness. This article concludes by staging an encounter between Rich and Gumbs at the bottom of the sea. Here, as part of a project of building refuge, Gumbs invites white feminism to welcome its own partial dissolution.